2019
DOI: 10.1155/2019/2904782
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Pediatric Osteochondral Fracture Dislocation of the Patella

Abstract: Pediatric osteochondral fracture dislocation of the patella is sometimes difficult to diagnose on the basis of physical examination or plain film radiography. Magnetic resonance imaging plays an important role in its early diagnosis, and early treatment can prevent damage to the articular cartilage as well as decrease the dislocation rate. Currently, many treatment choices have been reported with good results, but there is no consensus on which treatment option may lead to the best outcome. Herein, we describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In 1988, Rae and Khasawneh 17 were the first to successfully use headless cannulated compression screws to fix large osteochondral fragments of the patella. Other authors [7][8][9]18,19 have reported small series of cases and case reports, showing excellent outcomes in acute OCFs managed by ORIF with screw fixation. Gesslein et al, 20 in a series of 36 acute OCFs located on the patellar surface, concluded that fixation shows improved clinical outcomes and is superior as compared with debridement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1988, Rae and Khasawneh 17 were the first to successfully use headless cannulated compression screws to fix large osteochondral fragments of the patella. Other authors [7][8][9]18,19 have reported small series of cases and case reports, showing excellent outcomes in acute OCFs managed by ORIF with screw fixation. Gesslein et al, 20 in a series of 36 acute OCFs located on the patellar surface, concluded that fixation shows improved clinical outcomes and is superior as compared with debridement.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature regarding the management of acute patellar dislocation complicated by OCF consists mostly of case reports and small case series that report the results of various methods of osteochondral fragment fixation or excision. 3 4 5 6 7 8 9 The effect of time on the results of fixation is an essential question that remains unanswered. 4 With no established guidelines, management of chronic OCF remains debatable, yet intriguing.…”
mentioning
confidence: 99%
“…e chief symptoms include pain, swelling, restricted movement, and joint hydrops of knee joints [1]. e common APD imaging examination methods cover the X-ray, CT, and magnetic resonance imaging (MRI) examinations [2]. As compared with ordinary X-ray and CT examination, the MRI examination is featured by no radiation, multiparameter imaging, and high resolution for soft tissue, and it can obtain the different degrees of damage to bone, cartilage, synovium, ligament and other tissues, the extension and degree of the bone contusion, bone marrow edema and osteochondral damage of the patellofemoral joint, and the injury location and extent of the medial retaining ligament and medial collateral ligament of patella through a single scanning.…”
Section: Introductionmentioning
confidence: 99%
“…Classically, the treatment of OCFs include osteosynthesis of the fragment with different devices described in the literature, such as standard compression screws, headless compression screws, Herbert screws, bioabsorbable screws and pins, meniscus arrows, or sutures passed through complete bone tunnels. [6][7][8][9][10][11][12][13][14][15][16][17][18] Occasionally, when the subchondral bone or the fragment is too small for fixation or chronic, it has to be removed and managed with cartilage restorative techniques, such as debridement and/or micro/nanofractures, autologous chondrocyte implantation/ matrix-induced chondrocyte implantation, mosaicplasty, bone grafts and scaffolds, biomaterials or fresh osteochondral allograft, depending on the size and depth of injury. [19][20][21][22][23] The purpose of this Technical Note is to describe the one-stage osteochondral fracture repair technique with knotless anchors and interconnected crossing suture sliding loops, with no complete bone tunnels, no need for a second-stage surgery hardware removal, and suitable in certain cases (Table 1) and for different anatomic locations, such as patella, condyle, or trochlea defects.…”
mentioning
confidence: 99%
“…Classically, the treatment of OCFs include osteosynthesis of the fragment with different devices described in the literature, such as standard compression screws, headless compression screws, Herbert screws, bioabsorbable screws and pins, meniscus arrows, or sutures passed through complete bone tunnels. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 …”
mentioning
confidence: 99%